2011
DOI: 10.1111/j.1540-8175.2011.01393.x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of Left Ventricular End-Diastolic Pressure with Tissue Doppler Imaging in Patients with Mitral Regurgitation

Abstract: Background: The ratio of early transmitral flow velocity to mitral annulus early diastolic velocity (E/Ea) is a widely used noninvasive tool to estimate left ventricular end diastolic pressure (LVEDP). The aim of this study was to explore whether E/Ea ratio was a reliable index for the estimation of LVEDP in patients with mitral regurgitation (MR). Methods: Sixteen patients with nonischemic MR (primary MR group; 6 male, 58 ± 12 years) 51 patients with ischemic MR (secondary MR group; 29 male, 63 ± 9 years) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
(79 reference statements)
0
13
0
Order By: Relevance
“…Caution should be used when using E/e' in LV disorders such as hypertrophic cardiomyopathy27) and myocardial infarction,28) as the downward movement during diastole can be influenced by upward movement during systole 29)30). Conversely, the transmitral E measurement may be the source of misleading information in the setting of moderate to severe mitral regurgitation (MR)31) and severe LV dysfunction 25). In patients with constrictive pericarditis, LV diastolic properties are usually well preserved despite increased LV filling pressure, 32) and the positive correlation of e' with LV filling pressure leads to an inverse relationship between E/e' and LV filling pressure 33)…”
Section: Technical Considerationsmentioning
confidence: 99%
“…Caution should be used when using E/e' in LV disorders such as hypertrophic cardiomyopathy27) and myocardial infarction,28) as the downward movement during diastole can be influenced by upward movement during systole 29)30). Conversely, the transmitral E measurement may be the source of misleading information in the setting of moderate to severe mitral regurgitation (MR)31) and severe LV dysfunction 25). In patients with constrictive pericarditis, LV diastolic properties are usually well preserved despite increased LV filling pressure, 32) and the positive correlation of e' with LV filling pressure leads to an inverse relationship between E/e' and LV filling pressure 33)…”
Section: Technical Considerationsmentioning
confidence: 99%
“…In many previous studies about E/e 0 performed by Nagueh et al or Ommen et al, MR patients were excluded [4,17]. Some previous studies have reported on the estimation of PCWP by using mitral inflow in MR patients [1,5,18]. However, among several measurements using mitral inflow including E/A ratio, deceleration time, and isovolumic relaxation time to predict PCWP [19], the best correlations between Doppler measurements and PCWP were observed in patients without significant MR [17].…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, Van de Veire et al showed that E/e 0 was independently predicted by ischemic (secondary) MR severity [20]. On the other hand, Yesildag et al did not show that E/e 0 had any association with LVEDP in patients with secondary MR [1]. Agricola et al showed that E/e 0 was an independent predictor of LVEDP in primary MR [21].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations